Penerapan Strategi Pembelajaran Interaktif dalam Meningkatkan Hasil Belajar IPA di Kelas Vi SD - Idris Idris (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
The purpose of this study was to improve learning outcomes by using interactive learning strategis in the process of learning science class VI SDN 1 Riau Silip. The results of the study are as follows: (1) students involved appear active starting from Cycle I to Cycle III; (2) increasing student learning outcomes, namely mastery of students' concepts of learning material, namely starting from cycle I to Cycle III the average value of students increases so as to reach an average number of 87.83; and (3) in terms of student activeness, the average score obtained in Cycle III was 81.52 and in terms of student cooperation attitudes obtained an average score of 80.43 in Cycle III. Based on the results of learning, activeness, and cooperative attitudes obtained by students, it can be concluded that the application of interactive learning strategis can be used in learning in schools, especially learning to identify the functions of human respiratory organs in science subjects. Keywords: Interactive Learning Strategi, Learning Outcomes, Function of Human Respiratory Organ